PELATIHAN TEKNIK PRESENTASI MENGGUNAKAN POWERPOINT PADA ANAK USIA PENDIDIKAN DASAR DI LINGKUNGAN MASJID AL MU’MINUN RW-12 KELURAHAN LOWOKWARU KOTA MALANG - M. Noor Hidayat; Ferdian Ronilaya; Irwan Heryanto; Muhammad Fahmi Hakim; Rohmanita D (Jurnal Pengabdian Polinema Kepada Masyarakat, 2020)
Microsoft Office Power Point Training for Elementary School-aged Children in the Neighborhood of the Al Mu'minun Mosque RW-12 in Lowokwaru Village, Malang City, provides additional skills and motivation for elementary and middle school children to have the ability to operate and to use Microsoft Office Power Point software (MS Power Point). With the additional knowledge and expertise, these children are expected to be able to overcome problems related to their school assignments.